Religious Education as a Moderator of Social Media's Impact on Cyberbullying and Mental Health - Ghiyatuddin Muhammad Asfahani; Sadam Fajar Shodiq (Universitas PGRI Yogyakarta, 2026)
Social media is one of the innovations in today's technological advances. Various forms of convenience provided by social media make it the largest platform for helping users, including students, to communicate, discuss, or search for information virtually. However, the presence of social media also hurts its users, especially students. Therefore, this study aims to determine the extent to which social media use influences cyberbullying behavior and the mental health of students. And consider the significant role that religious education plays in moderating the use of social media. This study uses quantitative research methods using a Likert scale survey processed with SmartPLS. In this study, 236 students from two junior high schools were selected for sampling. The findings show that social media use has a significant effect on cyberbullying behaviour and students' mental health, while religious education only moderates the impact of social media on mental health. Thus, it is expected that this research will provide insight for parents, teachers, and students on the importance of religious education as a preventive factor in the wise use of social media. Keywords: social media, cyberbullying, mental health, religious education